2021
DOI: 10.1111/1758-5899.13005
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing Time and Space within the United Nations

Abstract: Departing from an objective understanding of time and space, this article investigates time and space together as daily individual and social experiences within the United Nations (UN) system. Focused on both staff members and civil society partners, it explores how experiences of time and space affect the way the UN functions. Based on two case studies, it first shows that time and space as they are experienced by individuals shape UN everyday practices pointing to a form of unlimited connectedness among indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 59 publications
1
22
0
1
Order By: Relevance
“…Yet, over its thirty years of existence, the IPCC has become more than a transnational network of experts and has witnessed an unprecedented institutionalization. While it is not legally an IO, it is an “IO progeny" and bears similarities with other United Nations bodies (Johnson, 2014; Kimber and Maertens, this issue). The IPCC is also an interesting case because it is often presented as a model for the production of global expert assessments.…”
Section: The Practices and Procedures Of International Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, over its thirty years of existence, the IPCC has become more than a transnational network of experts and has witnessed an unprecedented institutionalization. While it is not legally an IO, it is an “IO progeny" and bears similarities with other United Nations bodies (Johnson, 2014; Kimber and Maertens, this issue). The IPCC is also an interesting case because it is often presented as a model for the production of global expert assessments.…”
Section: The Practices and Procedures Of International Organizationsmentioning
confidence: 99%
“…The contrarians accused the IPCC of breaching its own rules by modifying the content of the chapter after it had been reviewed and formally approved by governments. Later investigations into the controversy revealed that the IPCC lacked a formal closure mechanism and that procedures neither allowed nor prohibited modifications after the approval session (Edwards and Schneider, 1997; Lahsen, 1999). Similar procedural disputes emerged in the approval of the WG III reports, when authors refused to remove controversial statements about the statistical value of human lives from their chapter (Masood and Ochert, 1995).…”
Section: Establishing a Processmentioning
confidence: 99%
“…First, the Swiss political authorities at different levels provide resources to the International Geneva. Second, this location impacts the temporality within the IO ecosystem in Geneva (Kimber and Maertens 2021).…”
Section: The Impact Of the Swiss National Contextmentioning
confidence: 99%
“…Articles here argue that taking these into account can help better understand the origins, the performance and the future of IOs (Dairon & Badache, this special issue). Such an attention to IOs’ spatiotemporal environment also displays a broader methodological function, such as facilitating the work of the researcher in accessing relevant fieldwork (Dairon & Badache, this special issue; Eckl, this special issue; Kimber & Maertens, this special issue). The contributions to this issue do so in an original way, applying a qualitative lens to IO studies with new and complementary case studies at different scales of IO presence – the local (Geneva), national (Haiti, Vietnam/Mozambique) and regional levels (Middle East) – and at various moments of an IO’s life – exceptional events (emergency relief interventions, international summits), annually‐organized conferences, regular coordination meetings.…”
Section: Time Space and International Organizations: Cyclical Dynamicsmentioning
confidence: 99%
“…What is more striking however is the difference in terms of consequences: the specific combination of a location and its temporal routine or a particular political schedule can result in very contrasting impacts. This disparity appears particularly strongly when it comes to individuals’ participation: time and space have a significant impact on who is participating in IO undertakings, de facto leaving aside some actors who cannot afford long‐haul travels or expensive rents (Dairon & Badache, this special issue; Kimber & Maertens, this special issue), or on the contrary allowing others to join (Eckl, this special issue). A less expected repercussion lies with the success of local actors in trying to capitalize on the role of time and space: while they may sometimes gain political power and concrete influence on IOs (Campos, this special issue; Dairon & Badache, this special issue), they can also be marginalized compared to distant stakeholders, such as donors and IOs’ headquarters, which succeed in imposing their rules at a distance (Verlin, this special issue).…”
Section: Time Space and International Organizations: Cyclical Dynamicsmentioning
confidence: 99%